2016
DOI: 10.1016/j.carbon.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

On the use of diatomite as antishrinkage additive in the preparation of monolithic carbon aerogels

Abstract: We have synthesized flexible monolithic carbon aerogels by incorporating diatomite as antishrinkage agent during the sol-gel polycondensation of the precursors. The materials displayed elastic properties and preserved their pristine dimensions upon densification by carbonization even after etching of the diatomite, due to the open pore structure of the siliceous additive in the material's matrix. The aerogels displayed a well-developed porous structure, confirming that the polymerization of the precursors is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In a previous study we reported the two-step synthesis of N-doped carbon aerogels based on the prepolymerization of melamine-resorcinol-formaldehyde (MRF) mixtures [26,27]. Regardless of the solution pH and M/R molar ratio, the hydrogels prepared by the conventional one-step route displayed essentially a microporous character, as opposed to the meso-/macroporous network of those prepared upon the prepolymerization of the precursors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study we reported the two-step synthesis of N-doped carbon aerogels based on the prepolymerization of melamine-resorcinol-formaldehyde (MRF) mixtures [26,27]. Regardless of the solution pH and M/R molar ratio, the hydrogels prepared by the conventional one-step route displayed essentially a microporous character, as opposed to the meso-/macroporous network of those prepared upon the prepolymerization of the precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The typical shrinkage of the monoliths after carbonization—due to the evolution of volatiles upon densification of the carbon matrix—is shown in Figure 6. Values up to a 30% reduction in volume are typically reached in RF and MRF aerogels (Table 3); this behavior is independent of the composition of the aerogels [27], although it is more pronounced for MRF formulations. For the samples CG-D and CG-DB prepared in the presence of diatomite, the carbonized disks preserved their dimensions, even after the removal of the siliceous skeleton, likely due to the open pore structure of the aerogels provided by the diatomite (Figure 5b), which would facilitate the evolution of the volatiles upon carbonization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomis-Berenguer et al [9] synthesized carbon xerogels with ultrahigh micro-and mesopores from the activation of polymeric resins prepared by polycondensation of resorcinol/formaldehyde mixtures in basic medium and subcritical drying. Macías et al [10] prepared flexible monolithic carbon aerogels by incorporating diatomite as anti-shrinkage agent during the solgel polycondensation of resorcinol and formaldehyde. However, the mechanical strength of the carbon aerogel is far from being able to meet the practical application requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported the successful polycondensation of resorcinol-formaldehyde mixtures in the presence of low amounts of additives (e.g., diatomite, carbon black), to render carbon gel/CB composites with enhanced electrical conductivity and mechanical features [25,26]. Aiming to evaluate the percolation threshold of carbon black in its role as conductive additive, we prepared a series of organic and carbon gels with a fixed molar ratio of reactants (R/F, R/C and R/W) and increasing amounts of CB additive.…”
Section: Synthesis Of the Materialsmentioning
confidence: 99%